Complete Genome Sequences of the Historical Legionella pneumophila Strains OLDA and Pontiac - Mercante, Jeffrey W. (Genome Announc, 2016)
Here, we report the complete genome sequences of Legionella pneumophila serogroup 1 strains OLDA and Pontiac, which predate the 1976 Philadelphia Legionnaires’ disease outbreak. Strain OLDA was isolated in 1947 from an apparent sporadic case, and strain Pontiac caused an explosive outbreak at a Michigan health department in 1968.